Promoting Mathematical Literacy using Desmos Polygraph - Faradillah Haryani; Yola Yaneta Harso (Southeast Asian Mathematics Education Journal, 2023)
Language plays a fundamental role in the teaching and learning of mathematics. Students rely on their literacy skills to comprehend problem-solving situations before applying their mathematical knowledge. Unfortunately, there have been numerous reports of illiteracy, particularly in the area of communication, which is one of the most important skills in mathematical literacy. The students' lack of experience connecting formal mathematical language with their everyday language is one factor contributing to their communication illiteracy. To address this issue, the current study uses Desmos Polygraph as a tool to promote mathematical literacy by encouraging a thorough understanding of formal language. Desmos Polygraph's effective use encourages students to use formal language and understand the relationship between formal and informal language. This study, on the other hand, is solely concerned with analyzing the language used in the activity. Further research could assess the student-teacher interaction during the Desmos Polygraph activity to determine other potential in enhancing mathematical literacy.